Depression in the next generation is related with maternal behaviors: A cross-comparison by alternating rat's mother care. - Ruixin Yong; Hongxia Chai; Lei Ran; Yuhao Li; Bei An (PLoS ONE, 2023)
This study investigated the potential impacts of depressive rats' maternal behavior as an early life stress on the outcome of offspring as an adulthood. Offspring from the same mother were divided into two groups, half of them were fostered or remained by a depressive mother, and the other half remained or fostered by a control mother, respectively. The results showed that offspring fostered by depressive mothers presented significant depressive behaviors. Meanwhile, depressive mothers engaged in more grooming during the light cycle, but less off-the-pup behavior during the dark phase. In conclusion, offspring exposed to a postnatal depressive maternal environment developed a depressive-like behavior. Contrarily, postpartum maternal behaviors play an essential role, which might determine the outcome of the next generation. Furthermore, the appropriate timing of postpartum maternal caring sequences, which might eliminate prenatal stressful influences, was recognized and might be a promising approach for reducing children's predisposition to mental disorders in their life time.